PERAN KEUNGGULAN KOMPETITIF MEMEDIASI ORIENTASI PASAR DENGAN INTERNASIONALISASI UKM MEBEL DI KABUPATEN BADUNG - Permata Sari, Ni Nengah Maya; Yasa, Ni Nyoman Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
This study focuses on the role of competitive advantage in mediating the effect of market orientation towards the internationalization of SMEs in the furniture industry sector, in order to conduct a comprehensive review of previous studies and through surveys to the owners or managers of SMEs furniture in Badung. This study uses a quantitative approach in the form of associative. The number of respondents in this study were 130 respondents. The Data collection methods used were interview and questionnaires. The analysis technique used to test the hypothesis of the research is Path Analysis and Sobel test. Results from this study indicate that the market orientation of positive and significant impact on competitive advantage, a competitive advantage significant positive effect on internationalization, a market orientation and significant positive effect on internationalization and a significant competitive advantage is able to mediate the effect of market orientation towards internationalization.
Keywords: market orientation, competitive advantage, internationalization